From sustainability to adaptation: Goldman Sachs' corporate real estate strategy. Issue 4 (18th May 2016) - Keenan, Jesse M.
Abstract : This paper is premised on a conceptual framework that attempts to draw theoretical and practical connections between sustainability, resilience and adaptation. The framework is explored through a case study of the corporate real estate (property) strategies of Goldman Sachs (a multinational investment banking and investment management company) developed over the course of the consolidation and development of its corporate headquarters. This case seeks to identify the existence and nature of the relationships by and between sustainable corporate real estate strategies, resilient operations planning and the firm's adaptive capacity. A secondary proposition seeks to evaluate whether the capacity of the firm to adapt and be resilient to changing conditions has been positively advanced by the firm's sustainable corporate real estate strategies. The findings support the proposition that these connections do exist, as well as the proposition that sustainability was promoting adaptive capacity and operational resilience. However, it remains an open question to what extent these practices and capacities are deterministic of one another. This paper sets the stage for future research that seeks to measure and model organizational adaptive capacity and to understand the potential co-benefits that may serve the interests of firms who struggle to rationalize the costs of sustainability.